2020
DOI: 10.1088/1757-899x/671/1/012061
|View full text |Cite
|
Sign up to set email alerts
|

A modified shank for below knee prosthesis

Abstract: A below knee (BK) prosthesis is a device used to compensate for missing limb segments in patients with BK amputations as an aid for locomotive and other daily activities It consists of three main parts: socket, shank, and artificial foot. The shank is merely a shaft of a suitable length to serve as a frame structure to transfer biomechanical forces between the socket and foot. In traditional BK prostheses, the shank is made from rigid metallic or composite material tube (Teflon), while in the current work, a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Thus, for those stated reasons lower amputation can occur at the knee, ankle, hip or at the extension parts in between the joints. 3 Prosthesis which is a customized artificial limb that can be employed to enhance residual limbs with amputation which can ease daily activities of the amputees should be used. 4 A prosthetic limb is composed of three primary parts; the socket, the extension, and the foot or hand.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, for those stated reasons lower amputation can occur at the knee, ankle, hip or at the extension parts in between the joints. 3 Prosthesis which is a customized artificial limb that can be employed to enhance residual limbs with amputation which can ease daily activities of the amputees should be used. 4 A prosthetic limb is composed of three primary parts; the socket, the extension, and the foot or hand.…”
Section: Introductionmentioning
confidence: 99%
“…Yassr Y. Kahtan worked on the modal analysis of below knee sockets using finite element software (ANSYS Workbench 15) [31]. Saif M. Abbas studied the fatigue characteristics with analysis modeling for a new resin with carbon fiber and nile glass of the above knee prosthetic socket [32,33].The research aims to study the properties of materials used to reinforce prosthetic limbs by replacing artificial fibers with natural fibers.…”
Section: Introductionmentioning
confidence: 99%
“…The three main components of the transtibial prosthesis are the socket, the pylon and the artificial foot. The pylon or the shank is a shaft with appropriate length that serves as a frame structure to transfer biomechanical forces between the socket and the foot [1,2]. In traditional below knee prosthesis, the pylon can be made from rigid metallic, polymeric or composite materials.…”
Section: Introductionmentioning
confidence: 99%
“…A modified version of metallic pylon with the incorporation of a rubber pad showed an internal stiffness and damping characteristics, that acted as shock and energy absorber. The modified pylon was tested in a below-knee amputated patient and results showed improvements in patient gait performance, notably better impact reduction and more effective loading rate [1]. A composite pylon using perlon fibers showed that the new prosthetic pylon has good mechanical properties, lighter than standard metal pylons, and more economically viable with respect to the standard metal pylon [5].…”
Section: Introductionmentioning
confidence: 99%